Pengaruh Suplementasi Serbuk Kunyit dalam Pakan terhadap Morfologi dan Warna Hati Burung Puyuh (Coturnix coturnix japonica) - Hadi Jaya Putra, Sukarman (Universitas Cokroaminoto Palopo, 2025)
This study aims to investigate the effect of dietary turmeric powder supplementation on liver morphology and coloration in Japanese quail (Coturnix coturnix japonica). A total of 60 healthy quails aged 4 weeks were randomly assigned into four treatment groups: control (P0), turmeric powder supplementation at 54 mg (P1), 108 mg (P2), and 216 mg (P3) per bird per day. The feeding trial lasted for 30 days. Liver samples were collected post-treatment for macroscopic observation, including size (weight and length), surface texture, tissue consistency, and color using a calibrated color chart. Results showed that P2 group exhibited the most optimal liver morphology, with increased weight and size, smooth surface, normal consistency, and reddish-dark coloration indicating good hepatic perfusion and metabolic status. In contrast, P3 group showed slight hardness and yellowish discoloration, suggesting mild hepatic stress due to excessive bioactive intake. Statistical analysis using one-way ANOVA and Duncan’s test confirmed significant differences (p < 0.05) among treatment groups. It can be concluded that turmeric powder at a dose of 108 mg/bird/day improves liver health in quails, demonstrating its potential as a natural hepatoprotective supplement in poultry feed.